Islamic Republic of Afghanistan : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative; Preliminary Document. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses the enhanced Heavily Indebted Poor Countries (HIPC) Initiative of the Islamic Republic of Afghanistan. Afghanistan's economy achieved a major recovery, with robust GDP growth from a low level. Afghanistan has made significant progress in some areas of human development. Health care coverage has increased with the Basic Package of Health Services (BPHS) available to about 90 percent of the population. Public institutions should be strengthened and economic governance improved to ensure that economic growth can be sustained.